A nano calcium carbonate surface modification composite process

CN122941204APending Publication Date: 2026-10-20JIANDE SHUANGCHAO CALCIUM IND CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611070079.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-17
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0004]为了克服上述现有技术的缺点,本发明的目的在于提供了一种纳米碳酸钙表面改性复合工艺,通过依次引入季铵盐含硫硅烷结构、KH570偶联结构以及聚醚/丙烯酸接枝层,在纳米碳酸钙表面构建稳定的有机—无机复合改性层,从而改善纳米碳酸钙易团聚、与高分子基体相容性差、界面结合力不足的问题,并进一步提高其在阻燃复合材料中的阻燃协效、抑烟、力学增强及抗菌抑菌效果

Benefits of technology

(1)纳米碳酸钙本身比表面积大、表面极性强,颗粒之间容易通过氢键作用、静电吸附或范德华力发生团聚,导致其在树脂、橡胶、涂料等有机体系中分散不均。本发明通过KH570和季铵盐含硫硅烷中间体共同对纳米碳酸钙进行表面处理,使纳米碳酸钙表面由亲水性、强极性状态转变为具有有机相容性的改性状态。硅烷水解后形成的硅醇基可与纳米碳酸钙表面的羟基或活性位点发生缩合或吸附作用,从而在颗粒表面形成稳定包覆层;同时,KH570中的有机链段和季铵盐含硫硅烷中的有机基团能够增加颗粒表面的空间位阻,削弱颗粒间直接接触和二次团聚,使改性后的纳米碳酸钙更容易均匀分散于高分子基体中。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

This invention relates to the field of inorganic nanofiller surface modification technology, and discloses a composite process for surface modification of nano-calcium carbonate. The process first prepares a bromine-containing intermediate by reacting a mercapto compound with 3-bromopropylene, then reacts it with a tertiary amine silane to form a quaternary ammonium salt sulfur-containing silane intermediate. This intermediate is then combined with KH570 and applied to the surface of nano-calcium carbonate to construct an organosilane composite modification layer. Finally, surface grafting is performed using 4-hydroxybutylvinyl polyether and acrylic acid to obtain surface-modified nano-calcium carbonate. This process can improve the dispersibility, interfacial bonding strength, and flame-retardant synergistic effect of nano-calcium carbonate in polymer systems, and is applicable to the fields of flame-retardant plastics, rubber, coatings, and adhesives.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of inorganic nanofiller surface modification technology, specifically a composite process for surface modification of nano-calcium carbonate. Background Technology

[0002] Polymer materials are widely used in plastics, rubber, coatings, adhesives, and wire and cable sheathing. However, most polymer materials are flammable and are prone to combustion, melting, dripping, and smoke release when heated or exposed to open flames, posing certain safety hazards. Therefore, flame retardants or flame-retardant synergistic fillers are usually added to polymer materials to improve their flame retardant properties, thermal stability, and safety in use.

[0003] In existing flame retardant systems, halogenated flame retardants have high flame retardant efficiency, but they are prone to producing harmful fumes during combustion; inorganic flame retardants such as aluminum hydroxide and magnesium hydroxide are more environmentally friendly, but their addition amount is large, which can easily affect the mechanical properties and processing performance of the material; phosphorus and nitrogen flame retardants and intumescent flame retardants have good charring effect, but they have problems such as uneven dispersion, insufficient interfacial bonding and poor migration resistance in some resin systems. Nano-calcium carbonate possesses characteristics such as small particle size, large specific surface area, low cost, and good filling and reinforcing effects, making it suitable as an inorganic synergistic filler in flame-retardant composite materials. During combustion, it can participate in the formation of the inorganic residue layer, contributing to improved char layer density and enhancing the synergistic effects of heat insulation, smoke suppression, and flame retardancy. However, unmodified nano-calcium carbonate has a highly polar surface, leading to easy particle agglomeration and poor dispersibility and compatibility in organic resins. This can easily cause interfacial defects within the material, affecting the uniformity of flame retardant distribution and the mechanical properties of the composite material. Currently, commonly used methods for surface modification of nano-calcium carbonate mostly employ single coatings with stearic acid, fatty acid salts, titanate coupling agents, aluminate coupling agents, or common silane coupling agents. While these methods can improve dispersibility to some extent, the stability of the modified layer is limited, and desorption is prone to occur during high-temperature processing or long-term use. Furthermore, they are difficult to simultaneously achieve flame retardant synergy, smoke suppression, and interface enhancement effects. Therefore, it is necessary to provide a nano-calcium carbonate surface modification composite process, which improves the dispersibility, interfacial bonding force and flame retardant synergistic effect of nano-calcium carbonate in flame retardant polymer systems by constructing a stable organic-inorganic composite modification layer on the surface of nano-calcium carbonate, thereby improving the overall performance of flame retardant composite materials. Summary of the Invention

[0004] To overcome the shortcomings of the prior art, the present invention aims to provide a nano-calcium carbonate surface modification composite process. By sequentially introducing a quaternary ammonium salt sulfur-containing silane structure, a KH570 coupling structure, and a polyether / acrylic acid graft layer, a stable organic-inorganic composite modification layer is constructed on the surface of nano-calcium carbonate. This improves the problems of easy agglomeration of nano-calcium carbonate, poor compatibility with polymer matrix, and insufficient interfacial bonding force, and further enhances its flame retardant synergy, smoke suppression, mechanical reinforcement, and antibacterial and bacteriostatic effects in flame retardant composite materials.

[0005] To achieve the above objectives, the present invention provides the following technical solution: a nano-calcium carbonate surface modification composite process, comprising the following steps: S1. Under nitrogen protection, pentaerythritol tetrakis(3-mercaptopropionic acid) and 3-bromopropene are added to dichloromethane solvent and mixed thoroughly. Then, 2-hydroxy-2-methylphenylacetone photoinitiator is added, and the light intensity is controlled at 55-60 mW / cm² under 365 nm ultraviolet light. 2 Irradiate at room temperature for 30-35 minutes. After the reaction is complete, remove the solvent by rotary evaporation under reduced pressure, wash and dry to obtain intermediate 1. S2. Add 3-(N,N-dimethylaminopropyl)trimethoxysilane and intermediate 1 to N,N-dimethylformamide solvent, stir and mix, and react. After the reaction is completed, cool to room temperature, slowly pour the reaction solution into ethyl acetate to precipitate, filter under reduced pressure, wash and dry to obtain quaternary ammonium salt sulfur-containing silane intermediate. S3. Add a mixture of ethanol and water in a volume ratio of 9:1 to the reaction flask, then add glacial acetic acid, nano-calcium carbonate, hydroquinone, KH570, and quaternary ammonium salt sulfur-containing silane intermediate in sequence. After sonication for 25-30 minutes, react at 75-80℃ for 20-24 hours. After cooling to room temperature, centrifuge and wash three times with ethanol. Finally, dry at 50℃ to obtain organosilane coupling agent modified nano-calcium carbonate. S4. Add a suspension of organosilane coupling agent modified nano-calcium carbonate, water, and 4-hydroxybutyl vinyl polyether to a reaction flask. After ultrasonic dispersion for 30-35 min, simultaneously add acrylic acid aqueous solution and ammonium persulfate aqueous solution as initiator at 55-60℃. After the addition is complete, raise the temperature to 75-80℃ and continue the reaction for 3-5 h. After the reaction is completed, cool to room temperature, centrifuge and wash, and then vacuum dry for 10-12 h to obtain surface-modified nano-calcium carbonate.

[0006] In the above reaction process, in step S1, pentaerythritol tetrakis(3-mercaptopropionic acid) and 3-bromopropylene undergo a mercapto-olefin click reaction under ultraviolet light and a photoinitiator to obtain intermediate 1 containing bromine reaction sites; in step S2, intermediate 1 undergoes a quaternization reaction with 3-(N,N-dimethylaminopropyl)trimethoxysilane to form a quaternary ammonium salt sulfur-containing silane intermediate; in step S3, KH570 and the quaternary ammonium salt sulfur-containing silane intermediate are hydrolyzed and combined with the surface of nano-calcium carbonate to form an organosilane modified layer on the particle surface; in step S4, under the initiation of ammonium persulfate, acrylic acid and 4-hydroxybutyl vinyl polyether undergo graft polymerization and are further connected to the surface of modified nano-calcium carbonate, finally forming a composite modified nano-calcium carbonate with a silane layer, a quaternary ammonium salt sulfur-containing structure and a polyether / acrylic acid graft layer.

[0007] Further, in S1, the molar ratio of pentaerythritol tetrakis(3-mercaptopropionic acid), 3-bromopropene, and 2-hydroxy-2-methylphenylacetone photoinitiator is 1:(4.0-4.8):(0.02-0.08).

[0008] Furthermore, in S2, the molar ratio of 3-(N,N-dimethylaminopropyl)trimethoxysilane to intermediate 1 is (4.0-5.2):1.

[0009] Furthermore, in S2, the reaction temperature is 75-80℃; the reaction time is 6-8h.

[0010] Further, in step S3, based on 100 mL of a mixed solution of ethanol and water, the amount of glacial acetic acid added is 0.2-1.0 mL, the amount of nano-calcium carbonate added is 10-30 g, the amount of hydroquinone added is 0.03-0.15 g, the amount of KH570 added is 0.5-2.5 g, and the amount of quaternary ammonium salt sulfur-containing silane intermediate added is 0.5-0.8 g.

[0011] Furthermore, in step S3, the drying time is 12 to 24 hours.

[0012] Further, in step S4, based on 10g of organosilane coupling agent modified nano-calcium carbonate, the amount of water added is 8-15mL, the amount of 4-hydroxybutyl vinyl polyether added is 8-12g, the acrylic acid aqueous solution is prepared by dissolving 1.2-2.0mL of acrylic acid in 15-25mL of water, and the initiator ammonium persulfate aqueous solution is prepared by dissolving 0.3-0.8g of ammonium persulfate in 15-25mL of water. Furthermore, in step S4, the dripping time is 3-3.5 hours.

[0013] Compared with the prior art, the present invention has the following beneficial technical effects: (1) Nano-calcium carbonate has a large specific surface area and strong surface polarity. The particles are prone to agglomeration through hydrogen bonding, electrostatic adsorption, or van der Waals forces, resulting in uneven dispersion in organic systems such as resins, rubbers, and coatings. This invention uses KH570 and quaternary ammonium salt sulfur-containing silane intermediates to jointly treat the surface of nano-calcium carbonate, transforming the surface of nano-calcium carbonate from a hydrophilic and strongly polar state to a modified state with organic compatibility. The silanol groups formed after silane hydrolysis can condense or adsorb with the hydroxyl groups or active sites on the surface of nano-calcium carbonate, thereby forming a stable coating layer on the particle surface. At the same time, the organic segments in KH570 and the organic groups in the quaternary ammonium salt sulfur-containing silane can increase the steric hindrance on the particle surface, weaken the direct contact and secondary agglomeration between particles, and make the modified nano-calcium carbonate easier to disperse uniformly in the polymer matrix.

[0014] (2) In this invention, a quaternary ammonium salt sulfur-containing silane intermediate is first prepared, and then synergistically applied to the surface of nano-calcium carbonate with KH570. This results in the particle surface simultaneously possessing a silane coupling structure, a sulfur-containing structure, a quaternary ammonium salt structure, and an organic active structure that can participate in subsequent grafting. This composite interface layer can enhance the wettability between nano-calcium carbonate and the organic matrix, and improve the interfacial bonding force through organic chain segment entanglement, polar interaction, or chemical grafting, thereby reducing the interfacial voids and stress concentration between the inorganic filler and the resin matrix. This can improve the problem of decreased mechanical properties of the material after the addition of filler, allowing nano-calcium carbonate to not only play a filling role but also exert interfacial reinforcement and toughening effects.

[0015] (3) This invention introduces sulfur-containing structures, quaternary ammonium salt structures, and polyether / acrylic acid grafted segments onto the surface of nano-calcium carbonate, making it no longer a simple inorganic filler, but a composite modified filler with flame-retardant synergistic function. During the heating and combustion process of the material, nano-calcium carbonate itself can participate in the formation of the inorganic residue layer, improving the inorganic support of the char layer; the sulfur-containing structure is conducive to promoting the cross-linking and densification of the char layer at high temperatures, thereby improving the flame-retardant efficiency of the material.

[0016] (4) The surface-modified nano-calcium carbonate prepared by the invention has certain antibacterial and bacteriostatic effects. The reason is that a quaternary ammonium salt sulfur-containing silane intermediate is introduced into the surface of the nano-calcium carbonate, so that the surface of the particles has a quaternary ammonium salt cation structure. This structure can electrostatically adsorb with the negatively charged bacterial cell membrane, destroy the integrity of the cell membrane, and cause the cell contents to leak out, thereby inhibiting bacterial growth. At the same time, the quaternary ammonium salt group is fixed on the surface of the nano-calcium carbonate through the silane structure, and is not easy to migrate or be lost during processing and use, so it has good antibacterial durability. In addition, the modified nano-calcium carbonate has good dispersibility, which can make the antibacterial groups more evenly distributed in the composite material, thereby improving the overall antibacterial and bacteriostatic performance of the material. Detailed Implementation

[0017] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention are described clearly and completely. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0018] 3-(N,N-Dimethylaminopropyl)trimethoxysilane: CAS, 2530-86-1. KH570 is 3-methacryloyloxypropyltrimethoxysilane. 4-Hydroxybutylvinyl polyether, number average molecular weight Mn is 2400.

[0019] Example 1: This example provides a nano-calcium carbonate surface modification composite process, including the following steps: S1. Under nitrogen protection, 0.01 mol of pentaerythritol tetrakis(3-mercaptopropionic acid), 0.04 mol of 3-bromopropene, and 80 mL of dichloromethane were added to a reaction flask. After stirring and mixing evenly, 0.0002 mol of 2-hydroxy-2-methylphenylacetone photoinitiator was added. The reaction was carried out under 365 nm ultraviolet light irradiation, with the light intensity controlled at 55 mW / cm², and irradiated at room temperature for 30 min. After the reaction was completed, dichloromethane was removed by rotary evaporation under reduced pressure. The product was washed with deionized water and dried to obtain intermediate 1. S2. Add 0.04 mol of 3-(N,N-dimethylaminopropyl)trimethoxysilane, 10.01 mol of intermediate and 80 mL of N,N-dimethylformamide to the reaction flask, stir and mix, and heat to 75 °C for 6 h. After the reaction is completed, cool to room temperature, slowly pour the reaction solution into ethyl acetate to precipitate, filter under reduced pressure, wash with ethyl acetate and dry under vacuum to obtain the quaternary ammonium salt sulfur-containing silane intermediate. S3. Add 100 mL of a 9:1 volume ratio ethanol / water mixture to the reaction flask, then add 0.2 mL of glacial acetic acid, 10 g of nano-calcium carbonate, 0.03 g of hydroquinone, 0.5 g of KH570, and 0.5 g of quaternary ammonium salt sulfur-containing silane intermediate in sequence. After ultrasonic dispersion for 25 min, react at 75 °C for 20 h. After the reaction is completed, cool to room temperature, centrifuge, wash three times with ethanol, and dry at 50 °C for 12 h to obtain organosilane coupling agent modified nano-calcium carbonate. S4. Add 10g of organosilane coupling agent modified nano-calcium carbonate, 8mL of water, and 8g of 4-hydroxybutylvinyl polyether to the reaction flask. After ultrasonic dispersion for 30min, simultaneously add acrylic acid aqueous solution and ammonium persulfate aqueous solution at 55℃. The acrylic acid aqueous solution is prepared by dissolving 1.2mL of acrylic acid in 15mL of water, and the ammonium persulfate aqueous solution is prepared by dissolving 0.3g of ammonium persulfate in 15mL of water. The addition time is 3h. After the addition is completed, the temperature is raised to 75℃ and the reaction continues for 3h. After the reaction is completed, cool to room temperature, centrifuge, wash, and vacuum dry for 10h to obtain surface-modified nano-calcium carbonate.

[0020] Example 2: This example provides a nano-calcium carbonate surface modification composite process, including the following steps: S1. Under nitrogen protection, 0.01 mol of pentaerythritol tetrakis(3-mercaptopropionic acid), 0.044 mol of 3-bromopropene, and 90 mL of dichloromethane were added to a reaction flask. After stirring and mixing evenly, 0.0005 mol of 2-hydroxy-2-methylphenylacetone photoinitiator was added. The reaction was carried out under 365 nm ultraviolet light irradiation, with the light intensity controlled at 58 mW / cm², and irradiated at room temperature for 32 min. After the reaction was completed, dichloromethane was removed by rotary evaporation under reduced pressure. The product was washed with deionized water and dried to obtain intermediate 1. S2. Add 0.046 mol of 3-(N,N-dimethylaminopropyl)trimethoxysilane, 10.01 mol of intermediate and 90 mL of N,N-dimethylformamide to the reaction flask, stir and mix, and heat to 78 °C for 7 h. After the reaction is completed, cool to room temperature, slowly pour the reaction solution into ethyl acetate to precipitate, filter under reduced pressure, wash with ethyl acetate and dry under vacuum to obtain the quaternary ammonium salt sulfur-containing silane intermediate. S3. Add 100 mL of a 9:1 volume ratio ethanol / water mixture to the reaction flask, then add 0.6 mL of glacial acetic acid, 20 g of nano-calcium carbonate, 0.09 g of hydroquinone, 1.5 g of KH570, and 0.65 g of a quaternary ammonium salt sulfur-containing silane intermediate sequentially. After ultrasonic dispersion for 28 min, react at 78 °C for 22 h. After the reaction is complete, cool to room temperature, centrifuge, wash three times with ethanol, and dry at 50 °C for 18 h to obtain organosilane coupling agent modified nano-calcium carbonate. S4. Add 10g of organosilane coupling agent modified nano-calcium carbonate, 12mL of water, and 10g of 4-hydroxybutylvinyl polyether to the reaction flask. After ultrasonic dispersion for 32min, simultaneously add acrylic acid aqueous solution and ammonium persulfate aqueous solution at 58℃. The acrylic acid aqueous solution is prepared by dissolving 1.6mL of acrylic acid in 20mL of water, and the ammonium persulfate aqueous solution is prepared by dissolving 0.5g of ammonium persulfate in 20mL of water. The addition time is 3.2h. After the addition is completed, the temperature is raised to 78℃ and the reaction continues for 4h. After the reaction is completed, cool to room temperature, centrifuge, wash, and vacuum dry for 11h to obtain surface-modified nano-calcium carbonate.

[0021] Example 3: This example provides a nano-calcium carbonate surface modification composite process, including the following steps: S1. Under nitrogen protection, 0.01 mol of pentaerythritol tetrakis(3-mercaptopropionic acid), 0.048 mol of 3-bromopropene, and 100 mL of dichloromethane were added to a reaction flask. After stirring and mixing evenly, 0.0008 mol of 2-hydroxy-2-methylphenylacetone photoinitiator was added. The reaction was carried out under 365 nm ultraviolet light irradiation, with the light intensity controlled at 60 mW / cm², and irradiated at room temperature for 35 min. After the reaction was completed, dichloromethane was removed by rotary evaporation under reduced pressure. The product was washed with deionized water and dried to obtain intermediate 1. S2. Add 0.052 mol of 3-(N,N-dimethylaminopropyl)trimethoxysilane, 10.01 mol of intermediate and 100 mL of N,N-dimethylformamide to the reaction flask, stir and mix, and heat to 80 °C for 8 h. After the reaction is completed, cool to room temperature, slowly pour the reaction solution into ethyl acetate to precipitate, filter under reduced pressure, wash with ethyl acetate and dry under vacuum to obtain the quaternary ammonium salt sulfur-containing silane intermediate. S3. Add 100 mL of a 9:1 volume ratio ethanol / water mixture to the reaction flask, then add 1.0 mL of glacial acetic acid, 30 g of nano-calcium carbonate, 0.15 g of hydroquinone, 2.5 g of KH57O, and 0.8 g of quaternary ammonium salt sulfur-containing silane intermediate in sequence. After ultrasonic dispersion for 30 min, react at 80 °C for 24 h. After the reaction is completed, cool to room temperature, centrifuge, wash three times with ethanol, and dry at 50 °C for 24 h to obtain organosilane coupling agent modified nano-calcium carbonate. S4. Add 10g of organosilane coupling agent modified nano-calcium carbonate, 15mL of water, and 12g of 4-hydroxybutylvinyl polyether to the reaction flask. After ultrasonic dispersion for 35min, simultaneously add acrylic acid aqueous solution and ammonium persulfate aqueous solution at 60℃. The acrylic acid aqueous solution is prepared by dissolving 2.0mL of acrylic acid in 25mL of water, and the ammonium persulfate aqueous solution is prepared by dissolving 0.8g of ammonium persulfate in 25mL of water. The addition time is 3.5h. After the addition is completed, the temperature is raised to 80℃ and the reaction continues for 5h. After the reaction is completed, cool to room temperature, centrifuge, wash, and vacuum dry for 12h to obtain surface-modified nano-calcium carbonate.

[0022] Comparative Example 1 The difference between this comparative example and Example 3 is that no quaternary ammonium salt sulfur-containing silane intermediate is added in step S3, and only KH570 is used to treat the surface of nano-calcium carbonate. The amount of other raw materials and process conditions are the same as in Example 3. Specifically, in step S3, 100 mL of a 9:1 volume ratio ethanol / water mixture was added to the reaction flask, followed by 1.0 mL of glacial acetic acid, 30 g of nano-calcium carbonate, 0.15 g of hydroquinone, and 2.5 g of KH570. No quaternary ammonium salt sulfur-containing silane intermediate was added. After ultrasonic dispersion for 30 min, the mixture was reacted at 80 °C for 24 h. After the reaction, the mixture was cooled to room temperature, centrifuged, washed three times with ethanol, and dried at 50 °C for 24 h to obtain KH570 modified nano-calcium carbonate. Subsequent step S4 was performed under the same conditions as in Example 3. Comparative Example 2 The difference between this comparative example and Example 3 is that KH570 is not added in step S3, and only the quaternary ammonium salt sulfur-containing silane intermediate is used to treat the surface of nano-calcium carbonate. The amount of other raw materials and process conditions are the same as in Example 3. Specifically, in step S3, 100 mL of a 9:1 volume ratio ethanol / water mixture was added to the reaction flask, followed by 1.0 mL of glacial acetic acid, 30 g of nano-calcium carbonate, 0.15 g of hydroquinone, and 0.8 g of a quaternary ammonium salt sulfur-containing silane intermediate. KH570 was not added. After ultrasonic dispersion for 30 min, the mixture was reacted at 80 °C for 24 h. After the reaction, the mixture was cooled to room temperature, centrifuged, washed three times with ethanol, and dried at 50 °C for 24 h to obtain quaternary ammonium salt sulfur-containing silane-modified nano-calcium carbonate. Subsequent step S4 was performed under the same conditions as in Example 3. Comparative Example 3 The difference between this comparative example and Example 3 is that after completing step S3, the grafting reaction in step S4 is not performed. Instead, the nano-calcium carbonate modified by the organosilane coupling agent obtained in step S3 is used directly as the final product. The amounts of other raw materials and process conditions are the same as in Example 3. Specifically, intermediate 1 was prepared according to step S1 of Example 3, and a quaternary ammonium salt sulfur-containing silane intermediate was prepared according to step S2 of Example 3. Subsequently, organosilane coupling agent modified nano-calcium carbonate was prepared according to step S3 of Example 3. After step S3 was completed, the modified nano-calcium carbonate of Comparative Example 3 was obtained after centrifugation, washing with ethanol, and drying at 50°C for 24 hours. No further grafting reaction was performed with 4-hydroxybutyl vinyl polyether, aqueous acrylic acid solution, and aqueous ammonium persulfate solution.

[0023] I. Sample Preparation The surface-modified nano-calcium carbonate obtained in Examples 1-3 and Comparative Examples 1-3 were used as test samples. To evaluate its application effect in flame-retardant polymer materials, polypropylene flame-retardant composite materials were prepared according to the same formula: 70 parts polypropylene resin, 18 parts ammonium polyphosphate, 6 parts pentaerythritol, and 6 parts of the tested modified nano-calcium carbonate. After mixing the raw materials in each group for 5 minutes in a high-speed mixer, they were melt-blended and granulated through a twin-screw extruder. The temperatures in zones one to five were 170℃, 175℃, 180℃, 185℃, and 190℃, respectively, and the screw speed was 180 r / min. The resulting granules were dried at 80℃ for 4 hours and then used to prepare standard samples for flame retardant performance, mechanical properties, and antibacterial properties testing. Except for the source of the nano-calcium carbonate, the formulas, processing temperatures, and molding conditions of the test samples were kept consistent.

[0024] 1. Flame retardant performance test Limiting oxygen index test: The test was conducted according to GB / T 2406.2 "Determination of flammability by oxygen index method for plastics - Part 2: Room temperature test". The sample size was 100mm × 10mm × 4mm, and 5 samples were tested in each group, and the average value was taken. The higher the oxygen index, the higher the oxygen concentration required for the material to sustain combustion, and the better the flame retardant performance. Vertical burning test: The test was conducted according to GB / T 2408-2021 "Determination of flammability of plastics - Horizontal and Vertical Methods". The sample size was 125mm × 13mm × 3.2mm. The flaming time, dripping, and ignition of the absorbent cotton were recorded after each ignition, and the flame retardant rating was determined. Cone calorimetry test: The test was conducted according to ISO 5660-1, with a sample size of 100mm × 100mm × 3mm and an external heating radiant flux of 35kW / m². The peak heat release rate, total heat release, and total smoke release were recorded. The lower the peak heat release rate and total smoke release, the lower the heat release intensity and smoke release of the material during combustion. 2. Mechanical property testing Tensile property test: The test was conducted in accordance with GB / T 1040.2 "Determination of tensile properties of plastics - Part 2: Test conditions for molded and extruded plastics". Type 1A dumbbell-shaped specimens were used, the tensile speed was 50 mm / min, and 5 specimens were tested in each group and the average value was taken. Bending performance test: The test was conducted in accordance with GB / T 9341 "Determination of bending performance of plastics". The sample size was 80mm×10mm×4mm, the span was 64mm, the test speed was 2mm / min, and 5 samples were tested in each group and the average value was taken.

[0025] 3. Antibacterial performance test The antibacterial properties were tested according to GB / T 31402-2023 "Determination of antibacterial activity of plastics and other non-porous materials". Escherichia coli and Staphylococcus aureus were selected as the test strains, and the bacterial concentration was adjusted to approximately 1×10⁻⁶. 5 CFU / mL. Add the bacterial suspension dropwise to the sample surface and cover with a sterile film to ensure full contact between the bacterial suspension and the sample surface. Incubate for 24 hours at 35°C and a relative humidity of not less than 90%. After incubation, thoroughly wash away bacteria from the sample surface with elution buffer, perform serial dilutions, spread the solution, and incubate. Count the colonies. The antibacterial rate is calculated using the following formula: Antibacterial rate = (number of colonies in blank control sample - number of colonies in test sample) / number of colonies in blank control sample × 100%.

[0026] 4. Dispersion particle size test: Weigh 0.10g of the sample and add it to 100mL of anhydrous ethanol. After ultrasonic dispersion for 10min, use a laser particle size analyzer to test the D50 particle size of the dispersion system. The smaller the D50, the lower the degree of agglomeration of the modified nano-calcium carbonate and the better the dispersibility.

[0027] Table 1: Tests for flame retardant properties, mechanical properties, and antibacterial properties

[0028] As shown in Table 1, the difference between Comparative Example 1 and Example 3 is that the quaternary ammonium salt sulfur-containing silane intermediate was not added in step S3; only KH570 was used for surface treatment of nano-calcium carbonate. Table 1 also shows that the limiting oxygen index of Comparative Example 1 was 29.6%, lower than the 32.7% of Example 3. Its vertical combustion rating decreased from V-0 to V-1, and its peak heat release rate increased to 464 kW·m. - ², total smoke emissions increased to 1325 m²·m - ² This indicates that while using KH570 alone can improve the compatibility between nano-calcium carbonate and the polypropylene matrix, the synergistic effect of nano-calcium carbonate on the flame retardant system is significantly weakened due to the lack of sulfur-containing and quaternary ammonium salt structures. Sulfur-containing structures help promote cross-linking and densification of the char layer during combustion, and quaternary ammonium salt structures also help improve the polarity and functional distribution of the modified layer. Therefore, the flame retardant and smoke-suppressing effects of Comparative Example 1 are significantly inferior to those of the Example. From a mechanical property perspective, the tensile strength of Comparative Example 1 was 27.4 MPa, and the flexural strength was 41.2 MPa, both lower than those of Example 3 (29.7 MPa and 45.1 MPa). This is because, although KH570 can provide some silane coupling effect, the lack of the quaternary ammonium salt sulfur-containing silane intermediate results in an incomplete composite modified layer on the surface of the nano-calcium carbonate. Insufficient steric hindrance and interfacial interaction between particles easily lead to local agglomeration or uneven interfacial bonding, resulting in stress concentration points under stress and a decrease in tensile and flexural strength. Particularly concerning are the antibacterial data: the antibacterial rate against *Escherichia coli* in Comparative Example 1 was only 39.6%, and against *Staphylococcus aureus* was only 35.8%, far lower than the 98.1% and 97.0% of Example 3, indicating that the quaternary ammonium salt sulfur-containing silane intermediate is the main source of antibacterial performance. Without this component, the material surface lacks the quaternary ammonium salt cation structure capable of interacting with bacterial cell membranes, thus resulting in the most significant decrease in antibacterial effect. The difference between Comparative Example 2 and Example 3 is that KH570 was not added in step S3; only a quaternary ammonium salt sulfur-containing silane intermediate was used for surface treatment of nano-calcium carbonate. As shown in Table 1, Comparative Example 2 has a limiting oxygen index of 30.1%, a vertical combustion rating of V-1, and a peak heat release rate of 451 kW·m. - ², the total smoke emission was 1304 m²·m². - ², all are inferior to Example 3. This result indicates that although the quaternary ammonium salt sulfur-containing silane intermediate can introduce sulfur-containing and quaternary ammonium salt structures, contributing to flame retardancy and antibacterial properties, the lack of KH570 results in insufficient integrity of the silane coupling layer on the surface of the nano-calcium carbonate and insufficient binding ability with the organic resin. This leads to a decrease in the dispersibility of the filler in the polypropylene system, making it difficult to form a uniform and continuous synergistic system between the flame retardant and the modified nano-calcium carbonate. Therefore, the flame retardant and smoke suppression effects are lower than those of the Example. From a mechanical property perspective, Comparative Example 2 exhibits a tensile strength of 26.8 MPa and a flexural strength of 40.5 MPa, which are the lowest among the three comparative examples. This indicates that KH570 plays a crucial role in improving interfacial bonding. KH570 contains hydrolyzable silane groups and organic segments, which can act as a bridge between nano-calcium carbonate and the resin matrix. Without KH570, even with the presence of quaternary ammonium salt sulfur-containing silane structures on the particle surface, it is difficult to form a sufficiently stable and continuous interfacial bonding layer. This results in interfacial voids between the inorganic filler and the polypropylene matrix, making the material more prone to microcrack propagation under stress, thus leading to a decrease in mechanical properties. The antibacterial rate of Escherichia coli in Comparative Example 2 is 89.2%, and the antibacterial rate of Staphylococcus aureus is 87.6%, significantly higher than Comparative Example 1, but still lower than Example 3. This indicates that the quaternary ammonium salt structure can provide antibacterial effects, but due to the lack of dispersion and fixation effects provided by KH570, the distribution uniformity and stability of the antibacterial groups in the material are insufficient, ultimately resulting in an antibacterial rate lower than that of the fully composite modified examples. The difference between Comparative Example 3 and Example 3 is that the grafting reaction in step S4 was not performed after step S3, i.e., the grafted layer formed by 4-hydroxybutyl vinyl polyether and acrylic acid was not introduced. As shown in Table 1, Comparative Example 3 has a limiting oxygen index of 30.8%, a vertical flammability rating of V-1, and a peak heat release rate of 424 kW·m. - ², total smoke emission is 1240 m²·m - ². The data in this set are better than those in Comparative Examples 1 and 2, but still significantly lower than those in Example 3. This indicates that the co-treatment of KH570 with the quaternary ammonium salt sulfur-containing silane intermediate can bring about certain flame retardant synergistic and antibacterial effects. However, if the subsequent polyether / acrylic acid graft layer is lacking, the organic modification layer on the surface of the nano-calcium carbonate is still insufficient, and its dispersion stability and interfacial compatibility in the polypropylene flame retardant system are still inadequate. Therefore, the best flame retardant and smoke suppression effects cannot be achieved. From a mechanical property perspective, Comparative Example 3 exhibits a tensile strength of 27.8 MPa and a flexural strength of 42.0 MPa, which are slightly higher than Comparative Examples 1 and 2, but still lower than Example 3. This indicates that the grafting reaction in step S4 has a significant effect on further improving interfacial compatibility. After grafting with 4-hydroxybutylvinyl polyether and acrylic acid, flexible organic segments and polar interaction sites can be formed on the surface of nano-calcium carbonate. This improves the wettability and dispersibility of particles in the resin system and alleviates the rigidity difference between the inorganic filler and the resin matrix, thereby reducing internal defects in the material. Without this grafted layer, although nano-calcium carbonate already possesses a silane layer and a quaternary ammonium salt sulfur-containing structure, its surface organic segment length and steric hindrance are insufficient, and secondary agglomeration may still occur. Therefore, its mechanical properties and flame-retardant synergistic effect are both lower than those of the Example. The antibacterial rate of Escherichia coli in Comparative Example 3 was 91.5%, and the antibacterial rate of Staphylococcus aureus was 89.8%, which was higher than that of Comparative Example 1 but lower than that of Example 3. This indicates that although antibacterial groups are present, the lack of a grafting layer to improve dispersibility and the insufficient uniformity of the distribution of antibacterial active sites in the material lead to a decrease in the overall antibacterial effect.

[0029] It should be noted that, in this document, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus. Unless otherwise specified, an element defined by the phrase "comprising one..." does not exclude the presence of other identical elements in the process, method, article, or apparatus that includes said element.

[0030] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A nano-calcium carbonate surface modification composite process, characterized in that, Includes the following steps: S1. Under inert gas protection, pentaerythritol tetrakis(3-mercaptopropionic acid) ester, 3-bromopropene and photoinitiator were added to dichloromethane and mixed. The mixture was reacted under 365 nm ultraviolet light. After the reaction was completed, the solvent was removed, washed and dried to obtain intermediate 1. S2. Add 3-(N,N-dimethylaminopropyl)trimethoxysilane and intermediate 1 to N,N-dimethylformamide and mix to react. After the reaction is completed, the mixture is precipitated, filtered, washed and dried to obtain the quaternary ammonium salt sulfur-containing silane intermediate. S3. Add nano-calcium carbonate, KH570, quaternary ammonium salt sulfur-containing silane intermediate, glacial acetic acid and hydroquinone to an ethanol / water mixed solution, disperse by ultrasonication and then heat to react. After the reaction is completed, centrifuge, wash and dry to obtain organosilane coupling agent modified nano-calcium carbonate. S4. Organosilanes coupling agent-modified nano-calcium carbonate, 4-hydroxybutylvinyl polyether and water are mixed and dispersed, and then acrylic acid aqueous solution and ammonium persulfate aqueous solution are added dropwise to carry out the grafting reaction. After the reaction is completed, the nano-calcium carbonate is obtained by centrifugation, washing and vacuum drying.

2. The nano-calcium carbonate surface modification composite process according to claim 1, characterized in that, In S1, the molar ratio of pentaerythritol tetrakis(3-mercaptopropionic acid) ester, 3-bromopropene, and 2-hydroxy-2-methylphenylacetone photoinitiator is 1:(4.0-4.8):(0.02-0.08).

3. The nano-calcium carbonate surface modification composite process according to claim 1, characterized in that, In S2, the molar ratio of 3-(N,N-dimethylaminopropyl)trimethoxysilane to intermediate 1 is (4.0-5.2):

1.

4. The nano-calcium carbonate surface modification composite process according to claim 1, characterized in that, In the S2 reaction, the reaction temperature is 75-80℃ and the reaction time is 6-8h.

5. The nano-calcium carbonate surface modification composite process according to claim 1, characterized in that, In step S3, based on 100 mL of a mixed solution of ethanol and water, the amount of glacial acetic acid added is 0.2-1.0 mL, the amount of nano-calcium carbonate added is 10-30 g, the amount of hydroquinone added is 0.03-0.15 g, the amount of KH570 added is 0.5-2.5 g, and the amount of quaternary ammonium salt sulfur-containing silane intermediate added is 0.5-0.8 g.

6. The nano-calcium carbonate surface modification composite process according to claim 1, characterized in that, In step S3, the drying time is 12 to 24 hours.

7. The nano-calcium carbonate surface modification composite process according to claim 1, characterized in that, In step S4, based on 10g of organosilane coupling agent modified nano-calcium carbonate, the amount of water added is 8-15mL, the amount of 4-hydroxybutyl vinyl polyether added is 8-12g, the acrylic acid aqueous solution is prepared by dissolving 1.2-2.0mL of acrylic acid in 15-25mL of water, and the initiator ammonium persulfate aqueous solution is prepared by dissolving 0.3-0.8g of ammonium persulfate in 15-25mL of water.

8. The nano-calcium carbonate surface modification composite process according to claim 1, characterized in that, In S4, the dripping time is 3-3.5 hours.